Types and Frequencies of Written Corrective Feedbacks in Adult ESL Classroom - Wimbo Pambudi Wicaksono (Indonesian Journal of English Language Studies (IJELS), 2017)
Feedbacks have been seen as an effective way to help language learners acquire second language competence. This study aims to find out how the written corrective feedback (CF) has been used in the adult ESL classroom. In this study, the data were generated through the learner’s writing. Then the data were put into direct, coded and uncoded type of the written corrective feedback. In addition, those types of feedback were categorized into content and form category to find the scope of the written corrective feedback. As the result, the direct written corrective feedback was mostly used by the teachers. Interestingly, the teachers only used the uncoded written corrective feedback when it refers to the content of the writing. Besides, the dynamic corrective feedbacks that occur several times can be a proof that the teachers not only focus on the form the writing but also the content.